(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2024)
Iordan Iordanov passed away unexpectedly on October 3, 2021. His loss is deeply felt by the academic community and friends around the world. The current work provides an overview of his academic career and achievements and surveys his research in mathematics, economics and finance.